Involvement of a Specialist in Criminal Proceedings: A Defense Party’s Duty, Right or Opportunity - A. P. Bozhchenko; I. M. Nikitin (Теория и практика судебной экспертизы)
The article reviews the contradictions between the procedural law and an attorney’s professional duty to use an opinion of a knowledgeable person in the system of criminal procedure protection. The paper provides an analysis of the problems and difficulties arising in the implementation of this right in the criminal process leading to violation of the equality and adversarial principles: the optionality of the defense’s right to involve a specialist; the biased attitude of law enforcement agencies to the expert presented by the defense; the desire to diminish the probative value of the specialist’s conclusion and testimony; the absence of an obligation for an investigator and court in all cases to attach the expert’s opinion to the case. The author emphasizes how important it is for all the participants in the criminal process to understand the expert’s opinion and testimony’s independent evidentiary value. Proposals that contribute to the legal specificity and further development of the specialist institution within the framework of the fundamental principles of competition and equality of the parties are presented.